Ln2M2O7-based thermal protection material with high reflectivity and low thermal conductivity as well as preparation method and application of Ln2M2O7-based thermal protection material
By doping modified Ln2M2O7 based thermal protection material, it improves its reflectivity in the 0.4-6μm band, solving the problem of insufficient radiation heat transfer performance of existing materials in ultra-high temperature environments, and achieving high reflectivity and low thermal conductivity Comprehensive thermal insulation performance.
Patent Information
- Application Number
- CN202411262544.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-02-18
AI Technical Summary
The existing high-temperature thermal protection materials lack radiation heat transfer performance in ultra-high temperature environments, especially in the 0.4-6μm band, which leads to poor heat insulation effect.
By doping modified Ln2M2O7-based thermal protection materials, doped elements such as La, Gd, and Y are introduced to improve their reflectivity in the 0.4-6μm band and enhance radiation heat transfer performance.
The reflectivity and thermal insulation performance of Ln2M2O7-based thermal protection materials in high and ultra-high temperature environments have been significantly improved. The integral average reflectivity exceeds 70%, up to 75.4%, and the structure remains stable within the temperature range from room temperature to 1500℃.
Smart Images

Figure CN119462133A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of high temperature protection, in particular to high temperature radiation resistant heat protection materials, and more particularly to a high reflectivity, low thermal conductivity Ln2M2O7 (Ln=Gd, La, M=Zr, Hf) based heat protection material and its preparation method and application. Background Art
[0002] Thermal protection materials are a type of material that is specifically designed to provide effective thermal insulation and thermal protection in high temperature, flame or thermal radiation environments. These materials prevent thermal energy from damaging objects or systems by slowing down or reducing heat conduction and radiation. Their design and selection are usually based on their physical and chemical properties such as thermal conductivity, reflectivity, thermal expansion coefficient, high temperature resistance, chemical stability, and adaptability to specific environments. Among them, thermal barrier coating (TBC) materials used in the aerospace field and high-temperature pipeline insulation materials in the chemical industry are usually used in high temperature environments exceeding 1000°C, and some materials even need to be used in extreme ultra-high temperature environments exceeding 1500°C.
[0003] For thermal protection materials used in high-temperature environments, in addition to requiring them to have excellent properties such as low thermal conductivity, high melting point, high-temperature structural stability, and low oxygen permeability, they are also required to have high reflectivity in the visible and near-mid-infrared bands to resist radiative heat transfer at high temperatures. Studies have shown that radiative heat transfer through thermal protection materials in ultra-high temperature environments plays a vital role in the overall heat transfer process. Behind this phenomenon is the strong correlation between thermal radiation and temperature. According to the Stefan-Boltzmann law, thermal radiation is dependent on the fourth power of temperature, which makes thermal radiation a dominant heat transfer mechanism in ultra-high temperature environments.
[0004] In addition, the quantitative description of Planck's blackbody radiation law reveals the thermal radiation characteristics of objects at high temperatures. In ultra-high temperature environments, the energy of radiative heat transfer increases significantly and is mainly distributed in the visible and near-mid-infrared bands (0.4-6μm), which shows the importance of improving the reflectivity of thermal protection materials in this band for effectively coping with ultra-high temperature environments.
[0005] However, the traditional high-temperature thermal protection materials currently in service, such as yttria-stabilized zirconia (t'-YSZ) with a metastable tetragonal phase and carbon fiber reinforced carbon-based (C / C) composites, have certain defects. Current research shows that the longitudinal thermal conductivity of different types of C / C composites (such as carbon fiber and SiC nanofiber reinforced carbon-based composites) is between 5-30 W·m -1 ·K -1 The transverse thermal conductivity is between 15-180 W·m -1 ·K -1Its thermal conductivity is high and its thermal insulation effect is poor. Pure zirconium oxide undergoes a phase transition from monoclinic phase to tetragonal phase at about 1170°C, and the phase transition is accompanied by a 7% volume change. Yttria stabilizer can inhibit this process. YSZ thermal barrier coatings prepared by atmospheric plasma spraying and electron beam physical vapor deposition have a metastable tetragonal (t') phase, which is very stable below 1200°C. However, when the temperature exceeds 1200°C for a long time, the metastable tetragonal phase of t'-YSZ decomposes into cubic and tetragonal phases due to the diffusion of yttria. During cooling, the tetragonal phase further transforms into a monoclinic phase accompanied by a 7% volume expansion. The large volume change accompanying the phase transition process leads to increased stress, causing the YSZ coating to crack and fail. In addition, t'-YSZ is a translucent material in the 0.4-6μm band and cannot effectively resist radiation heat transfer at high temperatures.
[0006] At present, among the new materials for ultra-high temperature thermal protection, Ln2M2O7 (Ln = Gd, La, M = Zr, Hf) has a significantly high melting point, low thermal conductivity, high phase stability and good resistance to molten Ca-Mg-Al-silicate glass (CMAS) damage. Therefore, Ln2M2O7 ceramic material is one of the most promising ultra-high temperature thermal protection materials.
[0007] However, as a low thermal conductivity material, the reflectivity of Ln2M2O7 will be reduced accordingly due to the coupling effect. Summary of the invention
[0008] In view of the above technical problems, the present invention provides a high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection material and a preparation method and application thereof. Based on the Ln2M2O7 ceramic material with excellent thermal properties such as high melting point, low thermal conductivity and high thermal stability, appropriate doping elements are introduced into the open lattice of the Ln2M2O7 ceramic material, and its reflectivity in the 0.4-6μm band is significantly improved through doping modification, thereby effectively improving the radiation heat transfer performance and comprehensive thermal insulation performance of the Ln2M2O7-based thermal protection material in high temperature and ultra-high temperature environments.
[0009] To achieve the above object, the technical solution of the present invention is:
[0010] A high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection material, the chemical formula of the Ln2M2O7-based thermal protection material is (Ln 2-x A x )(M 2-y Ce y )O7, wherein Ln=La or Gd, M=Zr or Hf, A and Ce are doping elements, and A=Gd or La or Y, 0≤x<2, 0≤y<2;
[0011] The Ln2M2O7-based thermal protection material has a high reflectivity of 96.8% in the visible near-infrared band of 0.4-2.5 μm, and an integrated average reflectivity of more than 70% in the visible near-mid-infrared band of 0.4-6 μm.
[0012] In a preferred embodiment of the present invention, the chemical formula of the Ln2M2O7-based thermal protection material is (Gd 2-x La x )(M 2-y Ce y )O7.
[0013] In a preferred embodiment of the present invention, 0≤x≤0.3, 0≤y≤0.4. More preferably, 0<x≤0.1, 0.1≤y≤0.4. Furthermore, 0.02≤x≤0.06, 0.2≤y≤0.4.
[0014] Based on the same concept, the present invention also provides a method for preparing a doped modified Ln2M2O7-based thermal protection material, comprising the following steps:
[0015] S1: Submicron oxide powders (Gd2O3, La2O3, Y2O3, ZrO2, HfO2, CeO2) were weighed and mixed according to the stoichiometric ratio, and then high-energy ball milled at a speed of 300-400 r / min for 6-12 h using a planetary ball mill, with agate grinding balls and anhydrous ethanol as the ball milling media;
[0016] Then the powder slurry is placed in an electric hot air drying oven and dried at a temperature of 60-100° C. for 20-24 hours to fully evaporate the ethanol, and then ground in an agate mortar for 20-30 minutes to obtain a raw material powder with good dispersibility;
[0017] S2: placing the raw material powder processed in step S1 into a high-purity corundum crucible, and calcining it in a muffle furnace, and heating the muffle furnace to 1400-1600° C. at a heating rate of 3-5° C. / min, keeping the temperature for 12-24 hours, and cooling it at a cooling rate of 3-5° C. / min;
[0018] S3: The product obtained in step S2 is fully crushed and ground in an agate mortar, and then ball-milled again using a planetary ball mill. The ball-milling conditions are exactly the same as those in step S1;
[0019] After the ball milling is completed, the ball milling is dried, and the drying conditions are the same as those in step S1;
[0020] S4: Mix the powder treated in step S3 with an organic binder (such as a 5wt% polyvinyl alcohol (PVA) solution), grind it thoroughly in an agate mortar, and then place it in a mold for cold pressing to obtain a ceramic sheet. Then, keep it warm at 500-800°C for 1-2h to volatilize the organic binder, and sinter and keep it warm at 1430-1450°C for 10-12h to prepare a densified ceramic block of the doped modified Ln2M2O7-based thermal protection material, and heat or cool it at a rate of 3-5°C / min.
[0021] Based on the same concept, the present invention also provides a high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection coating, and the Ln2M2O7-based thermal protection coating is prepared from the Ln2M2O7-based thermal protection material.
[0022] Preferably, the Ln2M2O7-based thermal protective coating is prepared by a plasma spraying process.
[0023] Based on the same concept, the present invention also provides an application of the high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection material in the thermal protection field of preparing aircraft engine insulation layers, high-energy laser protection layers, and thermal insulation layers of high-temperature pipelines or reactors.
[0024] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art:
[0025] The doped Ln2M2O7-based thermal protection material provided by the present invention has a maximum reflectivity improvement of 8% compared to pure phase Ln2M2O7 in the mid-infrared band of 2.5-6μm, a high reflectivity of 96.8% in the visible near-infrared band of 0.4-2.5μm, and an integrated average reflectivity of more than 70% in the 0.4-6μm band, and can reach a maximum of 75.4%. Moreover, the thermal protection material has no phase change in the temperature range from room temperature to 1500℃, and the structure is stable. The full temperature range thermal conductivity from room temperature to 500℃ can be as low as 1.1-1.2W·m -1 ·K -1 and loses its correlation with temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The (Gd 2-x La x )XRD pattern of Zr2O7;
[0027] Figure 2 The (Gd 2-x La x )Reflectivity curve of Zr2O7;
[0028] Figure 3 The (Gd 1.75 La 0.25 ) Thermal conductivity-temperature line graph of Zr2O7 and Gd2Zr2O7;
[0029] Figure 4 The Gd2(Zr 2-y Ce y )XRD pattern of O7;
[0030] Figure 5 The Gd2(Zr 2-y Ce y ) Reflectivity curve of O7;
[0031] Figure 6 The (Gd 2-x La x )(Zr 2-y Ce y )O7 and (Gd 2-x Y x )Reflectivity curve of Zr2O7. DETAILED DESCRIPTION
[0032] The reason for the low reflectivity of Ln2M2O7 is that Ln2M2O7 is a ceramic material with low electrical conductivity. The contribution of free electrons to thermal conduction can be ignored. Therefore, only the effect of phonons on thermal conductivity is considered, that is, the lattice thermal conductivity is studied. For a pure phase ideal single crystal, its lattice thermal conductivity is decisively affected by phonon-phonon scattering (i.e., phonon intrinsic scattering). The more lattice vibration modes a material has and the more intense the intrinsic lattice vibration, the stronger the phonon scattering and the lower the thermal conductivity. The more lattice vibration modes a material has and the more intense the intrinsic lattice vibration, the stronger the coupling between phonons and photons. They will resonate, interact and exchange energy more frequently, which is manifested in the stronger absorption of light by the crystal and the lower the reflectivity.
[0033] According to Fresnel's law, the reflectivity of unpolarized light waves incident from a vacuum (or air) to the surface of a material is equal to half the sum of the reflectivities of perpendicular and parallel incident polarized light. In order to simplify the physical model and better explore the regulation principle of reflectivity, it is assumed that the light is incident perpendicularly. In addition, according to the electromagnetic wave transmission theory of light, when light propagates in a medium, the medium will always absorb the light, and its dielectric constant is a complex number, ε' is the real part, and ε" is the imaginary part. There is a quantitative positive correlation between the complex refractive index and the complex dielectric constant of the material.
[0034] According to the relevant knowledge of dielectric physics, the macroscopic and microscopic polarization laws of materials reveal that the former is proportional to the relative dielectric constant of the material, while the latter consists of three parts: electron cloud distortion polarization, ion displacement polarization and inherent dipole moment steering polarization.
[0035] In the band of 0.4-6μm, the polarization of the material is mainly related to the electron cloud distortion polarization and the ion displacement polarization. The effect of the inherent dipole moment steering polarization on the polarizability in this band is very small and can be ignored. Electron cloud distortion polarization refers to the fact that the electrons in the molecule are subjected to forces in the electric field, resulting in uneven distribution of the electron cloud and distortion, which causes the separation of positive and negative charges in the molecule as a whole, forming an electric dipole moment. Ion displacement polarization is the polarization phenomenon that occurs in ionic crystals under the action of an external electric field. Positive and negative ions are displaced or offset in opposite directions by the force of the electric field, thereby forming an electric dipole moment and causing the polarization of the material as a whole. This is similar to electron cloud distortion polarization, but it involves the movement of ions rather than the distortion of the electron cloud. From the intensity formulas of electronic polarization and ionic polarization, it can be seen that the intensity of electronic polarization and the intensity of ionic polarization are proportional to the cube of the ionic radius and the lattice constant, respectively. Therefore, by doping Ln2M2O7 with large-sized ions, its average ionic radius and lattice constant can be increased, thereby increasing the polarization strength of the Ln2M2O7-based thermal protection material to increase the real part of its complex dielectric constant and ultimately improve the reflectivity.
[0036] As an A2B2O7 type compound, Ln2M2O7 has a very open lattice, and its A and B positions can be replaced by atoms with similar chemical properties. For the A-position doping ion, all trivalent rare earth element ions can replace the original Ln 3+ And doped into the A-site lattice of Ln2M2O7. For the B-site doping ions, M 4+ It can be Zr 4+ 、Ce 4+ , Hf 4+ 、Ti 4+ One or more of them. 3+ or M 4+ Among all the ions, La 3+ and Ce 4+ has the largest ionic radius, while Gd 3+ It also has a larger ionic radius, so La 3+ , Gd 3+ and Ce 4+ The doping of Y can lead to a larger average ionic radius and lattice constant, and ultimately improve the reflectivity of Ln2M2O7-based thermal protection materials. In addition, the atomic number of Y is much smaller than that of lanthanide rare earth elements, so Y 3+ The atomic nucleus has a weaker binding ability to the outermost electrons, thereby increasing the electron polarization, which will also improve the reflectivity of the Ln2M2O7-based thermal protection material.
[0037] Therefore, the present invention selects four specific Ln2M2O7 (Ln = Gd, La, M = Zr, Hf) materials as the matrix and improves the reflectivity of the Ln2M2O7-based thermal protection material in the visible and near-infrared bands through doping modification to better transmit radiation heat at high temperatures. The chemical formula of the Ln2M2O7-based thermal protection material is (Ln 2-x A x )(M 2-y Ce y )O7, wherein Ln=La or Gd, M=Zr or Hf, La or Gd or Y is doped at the A position, Ce is doped at the B position, 0≤x<2, 0≤y<2.
[0038] According to existing research results, A2B2O7 compounds have two crystal structures: pyrochlore and defective fluorite. When the AB site ion radius ratio is greater than 1.22, the pyrochlore structure is generally formed, and vice versa, the defective fluorite structure is formed. For the case of Ln = Gd, M = Zr, due to Gd 3+ and Zr 4+ The ionic radii of La are 93.8 μm and 72 μm respectively, and their radius ratio is 1.3, so Gd2Zr2O7 can form a stable pyrochlore structure. 3+ and Ce 4+ When entering the AB lattice of Gd2Zr2O7 respectively, due to La 3+ and Ce 4+ The ionic radii of La are 106.1 μm and 92 μm respectively. 3+ The doping of Gd will lead to a larger AB site ion radius ratio. 2- x La x Zr2O7 can still form a stable pyrochlore structure. 4+ The doping of Gd2Zr will lead to a decrease in the AB site ion radius ratio, so when the doping amount is low, 2-y Ce y O7 forms a pyrochlore structure. As the doping amount increases, Gd2Zr 2-y Ce y O7 turns to form a defective fluorite structure. According to the law, Gd 2-x Y x Zr2O7、Gd 2-x La x Zr 2-y Ce y O7 and Gd 2-x Y x Zr 2-y Ce y The structure formed by O7 needs to be determined based on the average ionic radius of the AB positions.
[0039] The following is a further detailed description of a high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection material and its preparation method and application proposed by the present invention in conjunction with the accompanying drawings and specific embodiments. The advantages and features of the present invention will become clearer according to the following description.
[0040] Embodiment 1:
[0041] A La-doped modified Gd 2-x La x The preparation method of Zr2O7 (x=0.00, 0.02, 0.06, 0.10, 0.20, 0.25, 0.30) thermal protection material specifically comprises the following steps:
[0042] (1) Submicron-sized Gd2O3, La2O3, and ZrO2 raw material powders were weighed and mixed according to a stoichiometric ratio, and then subjected to high-energy ball milling at a speed of 300 r / min for 6 h using a planetary ball mill with agate grinding balls and anhydrous ethanol as the ball milling media.
[0043] (2) The powder slurry obtained in (1) was placed in an electric hot air drying oven and dried at 70° C. for 24 h to fully evaporate the ethanol, and then ground using an agate mortar for 30 min to obtain a raw material powder with good dispersibility.
[0044] (3) The raw material powder obtained in (2) is placed in a high-purity corundum crucible and calcined at 1400° C. for 12 h in a muffle furnace so that the mixed oxide raw material powder is fully reacted to generate the desired component Gd 2-x La x M2O7, the heating and cooling rate is controlled within 5℃ / min.
[0045] (4) The product obtained by calcination in (3) was fully crushed and ground in an agate mortar, and then ball-milled again using a planetary ball mill. The ball-milling conditions were exactly the same as in (1).
[0046] (5) The product powder slurry obtained in (4) is dried and ground to obtain a doped modified Gd 2- x La x The product powder of Zr2O7-based thermal protection material has the same drying and grinding conditions as in (2).
[0047] (6) Take 6 g of the product powder obtained in (5), then add 500 mg of 5 wt% polyvinyl alcohol (PVA) solution, and grind it thoroughly in an agate mortar. Then use a mold with a diameter of 30 mm and apply a pressure of 35 MPa for 2 minutes to cold press to obtain a ceramic sheet with a thickness of 2.0±0.1 mm.
[0048] (7) The ceramic body obtained in (6) is placed on a corundum support plate, and is kept at 600°C for 2 h in a muffle furnace to allow the PVA organic binder to fully volatilize, and then sintered and kept at 1430°C for 10 h to obtain a densified ceramic block of the doped modified thermal protection material, and the heating and cooling rate is controlled within 5°C / min.
[0049] Embodiment 2:
[0050] A Ce-doped modified Gd2Zr 2-y Ce y The preparation method of O7 (y=0.00, 0.05, 0.10, 0.15, 0.20, 0.30, 0.40) thermal protection material adopts submicron Gd2O3, ZrO2, CeO2 raw material powder, and the remaining steps are the same as Example 1.
[0051] Embodiment 3:
[0052] A La and Ce dual-element AB-site co-doping modified Gd 2-x La x Zr 2-y Ce y The preparation method of O7 (x=0.00, 0.10, y=0.00, 0.20, 0.40) thermal protection material adopts submicron Gd2O3, La2O3, ZrO2, CeO2 raw material powders, and the remaining steps are the same as Example 1.
[0053] Embodiment 4:
[0054] A Y-doped modified Gd 2-x Y x The preparation method of Zr2O7 (x=0.00, 0.10) thermal protection material adopts submicron Gd2O3, Y2O3, and ZrO2 raw material powders, and the remaining steps are the same as Example 1.
[0055] Embodiment 5:
[0056] The doped modified Ln2M2O7-based thermal protection material powder prepared in Examples 1-4 is selected as the ceramic layer, the NiCrAlY alloy powder is selected as the bonding layer, and the commercial Inconel718 alloy is selected as the substrate. The coating is prepared by atmospheric plasma spraying. The particle size distribution of the ceramic layer and the bonding layer powder is between 15-45 μm. The atmospheric plasma spraying process is a method of using a plasma flame to heat the powder to be sprayed to a molten or semi-molten state, impacting the surface of the substrate at high speed, and obtaining a layered coating after flattening and cooling. The coating prepared by the atmospheric plasma spraying process is a layered stacked porous structure with transverse interlayer pores and longitudinal cracks, and specifically includes the following steps:
[0057] (1) Processing the metal substrate: Clean the surface of the Inconel718 alloy to be sprayed, and perform roughening sandblasting on the surface to remove the oxide layer, so that the surface roughness reaches 1-30 μm, the sandblasting pressure is 0.6 MPa, the sandblasting distance is 80 mm, and the sand particle size is 46 mesh;
[0058] (2) Spraying bonding layer: spray NiCrAlY alloy powder on the surface of Inconel718 alloy, the powder feeding rate is 60g / min, and the spraying thickness is 150μm;
[0059] (3) Spraying ceramic layer: spraying doped modified Ln2M2O7-based thermal protection material ceramic powder on the surface of the bonding layer, with a powder feeding rate of 80 g / min and a spraying thickness of 500 μm;
[0060] (4) Further, when spraying the bonding layer and the ceramic layer, the spraying power is 42 kW, the spraying speed is 600 mm / s, the spraying distance is 100 mm, and the main gas flow rate is 40 L / min;
[0061] (5) Surface grinding and polishing: Grinding and polishing is performed on the surface of the ceramic layer to remove the spherical, pancake-shaped, and steamed bun-shaped protrusions formed on the sprayed surface. The surface structure of the ceramic layer after grinding and polishing is a wedge-shaped lamellar structure parallel to the coating surface. The ratio of the wedge thickness to the skin depth of the electromagnetic wave does not exceed 2.5. The secondary and higher-level reflections of the electromagnetic wave in the coating lamellar structure are used to reduce energy absorption. An automatic grinding and polishing machine is used for grinding and polishing. The grinding disc speed is 300r / min, the pressure is 15N, and the SiC sandpaper is used in turn. 400 mesh, 800 mesh, 1000 mesh, and 2000 mesh, the time is 30s each, and the rotation is in the same direction. The hairless polishing cloth has a speed of 200r / min, a pressure of 15N, a time of 180s, and a reverse rotation.
[0062] The Gd prepared in Example 1 2-x La x X-ray diffraction (XRD) phase analysis was performed on Zr2O7 (x = 0.00, 0.02, 0.06, 0.10, 0.20, 0.30). The results are as follows Figure 1 As shown. The XRD patterns of the prepared pure phase Gd2Zr2O7 and La-doped Gd2Zr2O7 ceramic blocks with different doping ratios were compared with the standard PDF card of Gd2Zr2O7 with pyrochlore structure (PDF#80-0470). It was found that all samples formed a single-phase pyrochlore structure. This is because Gd 3+ and Zr 4+ The ionic radii of La are 93.8 μm and 72 μm respectively, and their radius ratio is 1.3, which is larger than the AB site ionic radius ratio of 1.22 required for A2B2O7 compounds to form a stable pyrochlore structure.3+ The ionic radius of La is 106.1 μm. 3+ The doping of Gd 2- x La x Zr2O7 has a larger AB site ion radius ratio, so Gd 2-x La x Zr2O7 can still form a stable pyrochlore structure.
[0063] Furthermore, since all La-doped samples Gd 2-x La x Compared with pure Gd2Zr2O7, Zr2O7 has no impurity peak except for a slight shift in the peak position. 2-x La x The Zr2O7 sample did not undergo phase separation, which proves that the La element was successfully doped into the A-site lattice of Gd2Zr2O7.
[0064] Then the Gd prepared in Example 1 was tested 2-x La x The reflectivity of Zr2O7 (x = 0.00, 0.02, 0.06, 0.10, 0.20, 0.30) in the visible near-mid-infrared band is as follows Figure 2 By comparison Figure 2 Pure phase Gd2Zr2O7 and Gd with different La doping ratios 2-x La x The reflectivity of Zr2O7 ceramic blocks in the visible near-infrared band can be found to have the following conclusions and rules: In the visible near-infrared band of 0.4-2.5μm, all doped and modified Gd 2-x La x Zr2O7 ceramic blocks have a high reflectivity close to 100%. In the mid-infrared band, low-doping ratio La doped Gd 2-x La x The reflectivity of Zr2O7 ceramic blocks (x = 0.02, 0.06) increases successively. Compared with pure phase Gd2Zr2O7, the sample with x = 0.10 has a 10% increase in reflectivity in the wavelength range of 4-6μm, which may be due to La doping Gd 2-x La x The larger average ionic radius and lattice constant in the Zr2O7 ceramic bulk increase the real part of the complex dielectric constant.
[0065] Furthermore, in the mid-infrared band, high doping ratio of La doped Gd 2-x La xThe reflectivity of Zr2O7 ceramic blocks (x=0.20, 0.30) is lower than that of pure phase Gd2Zr2O7. This may be because the excessively high doping concentration leads to a higher crystal defect concentration and lattice distortion, which intensifies the lattice vibration, thereby enhancing infrared absorption and reducing reflectivity.
[0066] The Gd prepared in Example 1 was further tested. 1.75 La 0.25 The thermal conductivity of Zr2O7 and pure phase Gd2Zr2O7 from room temperature to 500℃ is shown in Figure 3 As shown in the figure, pure phase Gd2Zr2O7 and 12.5% La doped Gd 1.75 La 0.25 The thermal conductivity data of Zr2O7 ceramic blocks in the temperature range from room temperature to 500℃ show the following conclusions and rules: the thermal conductivity of pure phase Gd2Zr2O7 at room temperature to 500℃ increases with the increase of temperature from 1.73W·m -1 ·K -1 Reduced to 1.1W·m -1 ·K -1 About 12.5% La doped Gd 1.75 La 0.25 The thermal conductivity of Zr2O7 does not change significantly with temperature. The thermal conductivity of Zr2O7 in the whole temperature range from room temperature to 500℃ is always maintained at 1.1-1.2W·m -1 ·K -1 The lower level, its thermal conductivity at lower temperatures is significantly lower than that of pure phase Gd2Zr2O7, that is, La doping effectively reduces the thermal conductivity of Gd2Zr2O7-based thermal protection materials in the lower temperature range, making the thermal conductivity-temperature curve parallel to the temperature axis, so that its thermal conductivity loses its correlation with temperature. Therefore, La doping Gd2Zr2O7 with a doping ratio of 12.5% 1.75 La 0.25 The thermal conductivity-temperature curve of Zr2O7 can be approximately regarded as a straight line parallel to the temperature axis.
[0067] It should be noted that heat transfer in low conductivity materials such as Ln2M2O7 is achieved through lattice vibration, that is, lattice thermal conductivity is considered. The quantization of lattice vibration is phonon. The phonon scattering intensity, that is, the mean free path of phonon scattering, determines the lattice thermal conductivity of the material. The stronger the phonon scattering, the shorter the phonon mean free path and the lower the lattice thermal conductivity. The mean free path of phonon scattering in the material is determined by phonon-phonon inverse scattering, phonon-point defect scattering and phonon-grain boundary scattering. When other doping ions are introduced into the A position of Ln2M2O7, such as trivalent La 3+When the doping ions are present, they can form local resonances in the unusually large [MO6] octahedral "atomic cages" in the Ln2M2O7 crystal structure, thereby strongly scattering phonons and forming phonon-resonator scattering. Phonon-resonator scattering is a special and strong phonon-point defect scattering. When it exists, the phonon scattering mean free path of the material is mainly affected by phonon-resonator scattering. In addition, phonon-resonator scattering is a form of phonon scattering that is independent of temperature. Therefore, when Ln2M2O7 ceramic-based thermal protection materials have temperature-independent and strong phonon-resonator scattering, their thermal conductivity at lower temperatures will decrease and their thermal conductivity will lose its correlation with temperature.
[0068] Furthermore, by introducing La into the A-site of Gd2Zr2O7 3+ , a strong phonon scattering source can be introduced to make the La-doped Gd 1.75 La 0.25 The thermal conductivity of Zr2O7 at lower temperatures is significantly lower than that of pure phase Gd2Zr2O7, causing its thermal conductivity to lose its temperature dependence.
[0069] The Gd2Zr prepared in Example 2 2-y Ce y O7 (y = 0.00, 0.05, 0.10, 0.15, 0.20, 0.30, 0.40) was subjected to XRD phase analysis. The results are as follows Figure 4 The XRD patterns of the prepared pure phase Gd2Zr2O7 and Ce-doped Gd2Zr2O7 ceramic blocks with different doping ratios were compared with the standard PDF cards (PDF#80-0470 and PDF#80-0471) of Gd2Zr2O7 with pyrochlore structure and defective fluorite structure. It was found that the pure phase Gd2Zr2O7 and the low doping ratio Gd2Zr 2- y Ce y The O7 ceramic block forms a pyrochlore structure, but with the increase of Ce element doping ratio, Gd2Zr 2-y Ce y O7 ceramic bulk transforms into defective fluorite structure. Pure phase Gd2Zr2O7 can form a stable pyrochlore structure because Gd 3+ and Zr 4+ The ionic radii of Ce and Ce are 93.8 μm and 72 μm respectively, and their radius ratio is 1.3, which is larger than the AB ionic radius ratio of 1.22 required for A2B2O7 compounds to form a stable pyrochlore structure. 4+ The ionic radius of Ce is 92 μm. 4+ The doping of Gd2Zr 2-y Ce yThe average ion radius ratio of the AB position of the O7 ceramic block decreases, so the low doping ratio of Gd2Zr 2-y Ce y O7 ceramic blocks can still form pyrochlore structures. 4+ The doping amount of Gd2Zr 2-y Ce y The average AB ion radius ratio of O7 ceramic blocks is lower than the AB ion radius ratio of 1.22 required for A2B2O7 compounds to form a stable pyrochlore structure. 2-y Ce y The O7 ceramic block is then transformed into a defective fluorite structure that can still be formed.
[0070] Since all Ce-doped samples Gd2Zr 2-y Ce y Compared with pure Gd2Zr2O7, O7 has no impurity peak except for a slight shift in the peak position. 2-y Ce y The O7 ceramic block has a single-phase structure at the microscopic level, which proves that the Ce element is successfully doped into the B-site lattice of Gd2Zr2O7.
[0071] Then the Gd2Zr prepared in Example 2 was tested. 2-y Ce y The reflectivity of O7 (y = 0.00, 0.05, 0.10, 0.15, 0.20, 0.30, 0.40) in the visible near-mid-infrared band is as follows Figure 5 By comparison Figure 5 Pure phase Gd2Zr2O7 and Gd2Zr with different Ce doping ratios 2-y Ce y The reflectivity of O7 ceramic blocks in the visible near-infrared band can be found to be as follows: In the visible near-infrared band of 0.4-2.5μm, all doped and modified Gd2Zr 2-y Ce y O7 ceramic blocks have a high reflectivity close to 100%. In the mid-infrared band, Gd2Zr 2-y Ce y The reflectivity of the O7 ceramic block increases with the increase of the doping amount from 0.10 to 0.40. Compared with the pure phase Gd2Zr2O7, the sample with y = 0.40 has an 8% increase in reflectivity in the wavelength range of 4-6μm, which may be due to the Ce doping of Gd2Zr 2-y Ce y The larger average ionic radius and lattice constant in the O7 ceramic bulk lead to an increase in the real part of the complex dielectric constant.
[0072] The Gd prepared in Example 3 2-x La x Zr 2-y Ce y O7 (x = 0.00, 0.10, y = 0.00, 0.20, 0.40) and Gd prepared in Example 4 2-x Y x The reflectivity of Zr2O7 (x = 0.00, 0.10) was tested. Figure 6 By comparison Figure 6 The reflectivity of pure phase Gd2Zr2O7 and doped modified ceramic blocks in the visible near-mid-infrared band can be concluded as follows: In the visible near-infrared band of 0.4-2.5μm, all doped modified samples have a high reflectivity close to 100%. 1.9 La 0.1 Zr 1.6 Ce 0.4 O7 and Gd 1.9 Y 0.1 The reflectivity of Zr2O7 ceramic blocks is improved to varying degrees compared with that of pure Gd2Zr2O7, which may be due to the co-doping of La and Ce into Gd 1.9 La 0.1 Zr 1.6 Ce 0.4 The larger average ionic radius and lattice constant in the bulk O7 ceramics increase the real part of the complex dielectric constant or Y-doped Gd 1.9 Y 0.1 Y in Zr2O7 ceramic block 3+ This is because the atomic nucleus has a weaker ability to bind the outermost electrons, thereby increasing the polarization of the electrons.
[0073] The coating prepared by the atmospheric plasma spraying process in Example 5 was subjected to TG-DSC comprehensive thermal analysis in the temperature range from room temperature to 1500°C. The analysis shows that the coating prepared by the atmospheric plasma spraying process using the Ln2M2O7-based thermal protection material ceramic powder provided by the present invention has no phase change in the temperature range from room temperature to 1500°C and has a stable structure.
[0074] In addition, the integrated average reflectivity of ceramic blocks prepared by doping modified Ln2M2O7-based thermal protection materials with significantly improved reflectivity was calculated in the visible near-mid-infrared band of 0.4-6μm, when Ln=Gd and M=Zr. 2-x La x Zr2O7 ceramic bulk, 5%, 7.5%, 10%, 15% and 20% Ce-doped Gd2Zr 2-y Ce yO7 ceramic bulk, La, Ce co-doped with Gd 1.9 La 0.1 Zr 1.6 Ce 0.4 O7 bulk ceramic and Y-doped Gd 1.9 Y 0.1 The integrated average reflectivity of Zr2O7 ceramic blocks in this band exceeds 70%. 1.9 La 0.1 The integrated average reflectivity of the Zr2O7 ceramic block in the visible near-mid-infrared band of 0.4-6μm can reach 75.4%.
[0075] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Even if various changes are made to the present invention, if these changes fall within the scope of the claims of the present invention and their equivalents, they still fall within the protection scope of the present invention.
Claims
1. A high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection material, characterized in that: The chemical formula of the Ln2M2O7-based thermal protection material is (Ln 2-x A x )(M 2-y Ce y )O7, wherein Ln=La or Gd, M=Zr or Hf, A and Ce are doping elements, and A=Gd or La or Y, 0≤x<2, 0≤y<2; The Ln2M2O7-based thermal protection material has a high reflectivity of 96.8% in the visible near-infrared band of 0.4-2.5 μm, and an integrated average reflectivity of more than 70% in the visible near-mid-infrared band of 0.4-6 μm.
2. The high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection material according to claim 1, characterized in that: The chemical formula of the Ln2M2O7-based thermal protection material is (Gd 2-x La x )(M 2-y Ce y )O7.
3. The high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection material according to claim 1 or 2, characterized in that: 0<x≤0.1, 0.1≤y<2.
4. The high reflectivity, low thermal conductivity Ln2M2O7 based thermal protection material according to claim 3, characterized in that: 0.1≤y≤0.4。 5. A method for preparing a high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: weighing, mixing, ball milling and drying submicron oxide powders according to stoichiometric ratios; S2: calcining the raw material processed in step S1 in a high temperature furnace, and heating the high temperature furnace to 1400-1600°C at a heating rate of 3-5°C / min, keeping the temperature for 12-24h, and cooling at a cooling rate of 3-5°C / min; S3: ball-milling the product obtained in step S2 for a second time and drying it; S4: Mix and grind the powder treated in step S3 with an organic binder, and then cold-press to obtain a ceramic sheet, and then keep it at 500-800°C for 1-2h to volatilize the organic binder, and then sinter and keep it at 1430-1450°C for 10-12h to prepare a densified ceramic block of the Ln2M2O7-based thermal protection material, and heat or cool at a rate of 3-5°C / min.
6. The method for preparing the high reflectivity and low thermal conductivity Ln2M2O7-based thermal protection material according to claim 5, characterized in that: The organic binder is polyvinyl alcohol.
7. A high reflectivity, low thermal conductivity Ln2M2O7 based thermal protection coating, characterized in that: The Ln2M2O7-based thermal protection coating is prepared from the Ln2M2O7-based thermal protection material described in any one of claims 1-4.
8. The high reflectivity, low thermal conductivity Ln2M2O7 based thermal protection coating according to claim 7, characterized in that: The Ln2M2O7-based thermal protection coating is prepared by an atmospheric plasma spraying process.
9. An application of the high reflectivity, low thermal conductivity Ln2M2O7-based thermal protection material as described in any one of claims 1 to 4 in the preparation of thermal insulation layers for aircraft engines, high-energy laser protection layers, and thermal insulation layers for high-temperature pipelines or reactors.
Citation Information
Patent Citations
Ceramic material for high-temperature-resistant thermal barrier coating and preparation method thereof
CN102659403A
Solid solution type [La(2-x)Gdx] [Zr(2-y)Cey]O7 heat insulating ceramic and preparation method thereof
CN103787659A
Co-doped modified pyrochlore thermal-barrier coating material with ultralow thermal conductivity and preparation method of co-doped modified pyrochlore thermal-barrier coating material
CN112960980A